Preventive Management for Occupational Diseases in Battery Industry - Febri Endra Budi Setyawan; Amalia Wahyu Natasari; Nesrin Zaharah; Divi Aditya Romadhona Putra; Wafiyah Hasanah; Ronty Birnanda Ramadhona (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2021)
Abstract—Occupational disease are important topic since they often occur in a long period of time. The purpose of this article is to find out how to prevent occupational diseases in the battery industry. This research is a systematic review of articles obtained through manual search engines from Google Scholars, Proquest, PubMed, Research Gate and has been published nationally and internationally in 2015-2020. The results of a systematic review were obtained from 30 scientific articles that were published nationally and internationally in 2015-2020 related to the battery industry process and related to occupational diseases. The factors contributing are varies from enviromental, biological, ergonomic, and the workers itself. There are several preventive management that can be done according to the analysis of the possible diseases that can be occured. Workers in the battery industry can experience occupational diseases, including: allergic contact dermatitis, bacterial conjunctivitis, noise-induced hearing loss, Low Back Pain and Carpal tunnel syndrome. Some prevention efforts that can be done include: using personal protective equipment, detecting workers who have a history of DKA, maintaining hygiene and cleanliness of the work environment, using furniture that is in accordance with ergonomic standards and not lifting heavy loads, reducing repetitive pressing movements and doing regular exercise.Keywords: preventive, allergic contact dermatitis, conjungtivitis, nihl, lbp, cts, battery industry Abstrak—Penyakit akibat kerja menjadi perhatian penting karena muncul dalam jangka waktu panjang sehingga harus dilakukan upaya pencegahan penyakit. Penelitian ini merupakan review sistematik artikel yang diperoleh melalui melalui mesin pencari manual dari Google Scholars, Proquest, PubMed, Research Gate dan telah terpublikasi nasional maupun internasional pada tahun 2015-2020. Hasil review sistematik diperoleh dari 30 artikel ilmiah yang telah terpublikasi nasional maupun internasional pada tahun 2015-2020 yang terkait dengan proses industry baterai dan terkait dengan penyakit akibat kerja. Faktor penyebabnya juga berbagai macam karena faktor lingkungan, biologi, ergonomi, ataupun dari faktor pekerja. terdapat beberapa upaya preventif yang dapat disesuaikan dengan kemungkinan penyakit akibat kerja yang mungkin akan timbul. Pekerja di industri baterai dapat mengalami penyakit akibat kerja, antara lain: dermatitis kontak alergi, konjungtivitis bakteri, gangguan pendengaran akibat kebisingan, Low Back Pain dan Carpal tunnel syndrome. Beberapa upaya pencegahan yang dapat dilakukan antara lain: menggunakan alat pelindung diri, mendeteksi pekerja yang memiliki riwayat DKA, menjaga kebersihan dan kebersihan lingkungan kerja, menggunakan furnitur yang sesuai dengan standar ergonomis dan tidak mengangkat beban berat, mengurangi penekanan berulang. gerakan dan melakukan olahraga teratur.Kata Kunci: preventif, dermatitis kontak alergi (dka), konjungtivitis, nihl, lbp, cts, industri baterai